Łódź as an arena of grand sport events: selected examples - Włodarczyk, Bogdan (Turyzm/Tourism, 2016)
The paper presents Łódź as a city where major sports events are held. Several sports facilities are featured which make it possible to organize various kinds of events, including international ones. In recent years, based on the existing infrastructure, several such events, for instance European or world championships, have been held in Łódź. The city is also perceived as a leading centre for volleyball competitions (league matches, Champions League, World League, European Championship, World Championship).